Jødetysk, jargon, jiddisk: The history of a glottonym in light of Language Making processes on Norwegian soil - Hårstad, Stian (Målbryting, 2022)
A crucial component of the cultural import that accompanied the immigration of so-called “Jews of the East” (Ger. “Ostjuden”) to Norway in the latter half of the 19th century was the language used by the majority of this group, what we today know as Yiddish. There is much evidence, however, that both the language and the glottonym were relatively vague terms for most Norwegians well into the 20th century, and the article attempts to map how “the language of the Jews” was referred to in this national minority’s early phase. This gives us insights into which sociolinguistic conceptualisations arose when facing a linguistic phenomenon that most people considered unfamiliar. A wide range of written sources, primarily mass media texts such as newspapers, magazines, and periodicals, have been scrutinized with particular attention to the terms used for “Jewish language” in a Norwegian context. This review paints a picture of a protracted process of Language Making, where an uncontested glottonym took decades to establish. One reason for this appears to be the fact that this linguistic practice’s status as a language has persistently been called into question. The data also reveals that the dawdling consolidation of Yiddish in Norway is connected with tendencies in the contemporaneous international discussion of Jewish language and culture.
Keywords: glottonyms; Yiddish; Language Making; minority languages; Jewish culture